The influence of pulmonary vascular pressures on lung diffusing capacity during incremental exercise in healthy aging. Issue 2 (25th January 2018) - Coffman, Kirsten E.; Curry, Timothy B.; Dietz, Niki M.; Chase, Steven C.; Carlson, Alex R.; Ziegler, Briana L.; Johnson, Bruce D.
Abstract: Alveolar‐capillary surface area for pulmonary gas exchange falls with aging, causing a reduction in lung diffusing capacity for carbon monoxide (DLCO). However, during exercise additional factors may influence DLCO, including pulmonary blood flow and pulmonary vascular pressures. First, we sought to determine the age‐dependent effect of incremental exercise on pulmonary vascular pressures and DLCO. We also aimed to investigate the dependence of DLCO on pulmonary vascular pressures during exercise via sildenafil administration to reduce pulmonary smooth muscle tone. Nine younger (27 ± 4 years) and nine older (70 ± 3 years) healthy subjects performed seven 5‐min exercise stages at rest, 0 (unloaded), 10, 15, 30, 50, and 70% of peak workload before and after sildenafil. DLCO, cardiac output ( Q ), and pulmonary artery and wedge pressure (mPAP and mPCWP; subset of participants) were collected at each stage. mPAP was higher ( P  = 0.029) and DLCO was lower ( P  = 0.009) throughout exercise in older adults; however, the rate of rise in mPAP and DLCO with increasing Q was not different. A reduction in pulmonary smooth muscle tone via sildenafil administration reduced mPAP, mPCWP, and the transpulmonary gradient (TPG = mPAP–mPCWP) in younger and older subjects ( P  < 0.001). DLCO was reduced following the reduction in mPAP and TPG, regardless of age ( P  < 0.001). In conclusion, older adults successfully adapt to age‐dependent alterations in mPAP and DLCO. Furthermore, DLCO is dependent on pulmonary vascular pressures, likely to maintain adequate pulmonary capillary recruitment. The rise in pulmonary artery pressure with aging may be required to combat pulmonary vascular remodeling and maintain lung diffusing capacity, particularly during exercise. Abstract : We sought to determine the effect of incremental exercise on lung diffusing capacity and any dependence on pulmonary hemodynamics in younger and older individuals. We found that a reduction in pulmonary artery pressure hindered lung diffusing capacity during exercise, suggesting that a certain transpulmonary gradient is required to maintain sufficient pulmonary capillary recruitment and thus lung surface area for gas exchange. Interestingly, these results were similar regardless of age.